Hubungan Kadar Hemoglobin Dengan Prestasi Belajar Pada Remaja Putri Di SMP Negeri 2 Pasaman Kabupaten Pasaman Barat - Hidayah Afnas, Nur; Silvia, Elwitri; Nurvalah, Nurvalah (Jurnal Medisains Kesehatan, 2023)
Anemia is a major nutritional problem in Indonesia. The prevalence of anemia in Indonesia based on the 2018 Riskesdas data is 32%. The prevalence of anemia in young women in West Pasaman Regency in 2022 is 19.7% and the Sukamenanti Health Center is 16.6%. The incidence of anemia will affect the learning achievement of young women. This study aims to determine the relationship between hemoglobin levels and learning achievement. The design of this study was cross-sectional with the population being all grade VIII students at SMP Negeri 2 Pasaman. The research was conducted at Pasaman 2 Public Middle School on March 1-7 2023. The sampling technique was simple random sampling with a total sample of 53 people. Collecting data by measuring hemoglobin levels to see the incidence of anemia and recapitulating the average results of report cards in odd semesters to see academic achievement. The data were processed statistically using the "Chi square" test with a 95% confidence level. The results showed that the learning achievement of 35 girls (66%) was low and the hemoglobin level in the anemia category was 31 students (58.5%). The results showed that there was a relationship between hemoglobin levels and the learning achievement of young women (p value = 0.018). The conclusion in this study is that there is a relationship between hemoglobin levels and learning achievement of young women at SMP Negeri 2 Pasaman, West Pasaman Regency. It is suggested that the school can work together with the puskesmas and the local health office to provide information about the importance of maintaining health in preventing the occurrence of anemia so that they can improve their academic achievement